Evaluating the physical properties of microwave-cured and heat-cured acrylic denture base materials after the addition of ZrO2 nanoparticles. - Radhwan H Hasan; Rana R Aziz; Marwah M Shehab; Jaafar Abduo (Journal of Baghdad College of Dentistry)
Background: The structural, physical, and mechanical properties of denture-based acrylic resin are still compromised by water sorption, water solubility, and porosity. These issues have long called for improved techniques, and the use of nanoparticles is one of them. The main objective of the current investigation was to evaluate and contrast some physical parameters (water sorption, water solubility, and porosity) after the incorporation of ZrO2 nanoparticles (0%, 3% and 5%) into heat-cured acrylic denture base materials (Ivoclare, Major) and microwave-cured acrylic (Acron MC). Materials and methods: A total of 60 resin specimens were manufactured, including 5 specimens for each concentration of ZrO2 NP (30 for porosity and 30 for water sorption and solubility). Followed the manufacturer's directions for preparing the sample of each material. Results: The results were analysed with descriptive statistics, Analysis of Variance(ANOVA) test, Duncan multiple range test, and independent T test demonstrated that the addition of nanoparticles (3% and 5%) decreased water sorption, water solubility, and porosity of PMMA(polymethyl methacrylate) for both types(microwave-cured and heat-cured acrylic denture base materials). Where, at 3%, the ZrO2 nanoparticles showed the best values for all tests compared to the control group. Conclusions: ZrO2 (3% and 5%) nanoparticle reinforcement of acrylic resin can be a useful tactic for lowering water sorption, solubility and porosity, thereby enhancing the performance of the material in various applications for microwave-cured and heat-cured acrylic denture base materials.